Depth of anaesthesia and mortality after cardiac or noncardiac surgery: a systematic review and meta-analysis of randomised controlled trials. (February 2023) - Payne, Thomas; Braithwaite, Hannah; McCulloch, Tim; Paleologos, Michael; Johnstone, Charlotte; Wehrman, Jordan; Taylor, Jennifer; Loadsman, John; Wang, Andy Y.; Sanders, Robert D.
Abstract: Background: Recent randomised controlled trials have failed to show a benefit in mortality by using processed electroencephalography (pEEG) to guide lighter anaesthesia. We performed a meta-analysis of mortality data from randomised trials of pEEG monitoring to assess the evidence of any protective effect of pEEG-guided light anaesthesia compared with deep anaesthesia in adults aged ≥18 yr. Methods: Our study followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. In February 2022, we searched three databases (Cochrane CENTRAL, OVID Medline, EMBASE) for RCTs of pEEG monitoring that provided mortality data at 30 days, 90 days, and/or 1 yr or longer. Results: We included 16 articles from 12 RCTs with 48 827 total participants. We observed no statistically significant mortality reduction with light anaesthesia compared with deep anaesthesia in patients aged ≥18 yr when all studies were pooled (odds ratio [OR]=0.99; 95% confidence interval (CI), 0.92–1.08). This result did not change significantly when analysing mortality at 30 days, 90 days, 1 yr or longer. We observed no mortality benefit for pEEG monitoring compared with usual care (OR=1.02; 95% CI, 0.89–1.18), targeting higher pEEG index values compared with lower values (OR=0.89; 95% CI, 0.60–1.32), or low pEEG index value alerts compared with no alerts (OR=1.02; 95% CI, 0.41–2.52). Conclusions: pEEG-guided lighter anaesthesia does not appear to reduce the risk of postoperative mortality. The absence of a plausible rationale for why deeper anaesthesia should increase mortality has hampered appropriate design of definitive clinical trials. Clinical trial registration: CRD42022285195 (PROSPERO).